NEUTROPHIL TO LYMPHOCYTE RATIO AS A PREDICTOR OF SEVERITY IN COLORECTAL ADENOCARCINOMA - Ali, Sundas; Shahab, Sumaiya; Rauf, Manal; Riaz, Syeda Kiran; Sheikh, Ahmareen Khalid; Tariq, Javera (Journal of Ayub Medical College Abbottabad, 2022)
Background: Colorectal cancers are slowly developing cancers of which more than 95% are adenocarcinomas, beginning in the mucus-producing glands lining the colon and rectum. In Pakistan, colorectal carcinoma is ranked as the seventh most common malignancy in men and the ninth most common in women with a male to female ratio of 9 to 1. This study aimed at investigating Neutrophil to Lymphocyte Ratio (NLR) as a potential marker for predicting severity of disease in terms of tumour histological grade in patients with pre-operative colorectal adenocarcinoma.Methods: Retrospective cross-sectional study design was adopted and this study was conducted at the Department of Pathology, Pakistan Institute of Medical Sciences Islamabad. Sixty patients of all age-groups and both genders, diagnosed as colorectal adenocarcinoma on histopathological examination of resected specimens, were selected by consecutive non-probability sampling. Separately, 60 healthy subjects, age and sex-matched, were selected as control.Results: Results revealed that the most common age group was 41-60 years showing 29 cases (48%) followed by the age group 61-80 years with 17 cases (28%). The most common site was the rectum having 24 cases (40%) followed by the right hemicolon with 13 cases (21.7%). The mean of neutrophil to lymphocyte ratio rose in direct proportion to the grade of colorectal carcinoma, showing a mean value of 4.5 in well differentiated low grade carcinoma, 5.0 in moderately differentiated and 6.0 in high grade poorly differentiated carcinoma. All patients had higher total leukocyte count, higher absolute neutrophil count, higher total neutrophil percentage and higher NLR as compared to their normal healthy counterparts.Conclusion: It is concluded that the NLR is directly proportional to tumour grade so it can be used preoperatively to assess whether the tumour is advanced so that it can be dealt with accordingly. This ratio can also be used as an independent screening marker for colorectal carcinoma since it shows very low levels in normal colonic epithelium.